PROBLEMS IMPLEMENTING THE 2013 CURRICULUM LEARNING ASSESSMENT DURING THE COVID-19 PANDEMIC - Ishmahani Sobarningsih; Dede Margo Irianto; Yeni Yuniarti (Universitas Pendidikan Indonesia, 2022)
This study aimed to investigate the implementation of learning assessment of Curriculum 2013 during the Covid-19 pandemic in 263 Rancaloa Elementary School. This was a qualitative research with a case study. The subjects of the research were three teachers of grade, two upper grade teacher and a lower grade teacher of 263 Rancaloa Elementary Schools. The main instrument was the human instrument. While supporting instruments used interview guid, tape recorder, and observation sheet. The data were analysed using interactive analysis Miles Huberman (data collection, reduction, display, and verification/conclude). The results indicate that (1) the implementation of learning assessment of Curriculum 2013 during the Covid-19 pandemic has not met standards. However, of the three teachers who became the subject of study, two teacher managed to carry outmet standards that was VA1 and VA2, (2) the problems of learning assessment of Curriculum 2013 during the Covid-19 pandemic include; facilities and infrastructure, teachers and parents understanding, teachers’ productivity, unpreparedness teachers and parents, (3) the teachers strategy in addressing the problem is the teacher collective and individual strategy.